Non-aromatizable androgens modulate the lipopolysaccharide induced expression of the P2X7 receptor in human adipocytes - Di Vincenzo, Angelo; Granzotto, Marnie; Crescenzi, Marika; Vettor, Roberto; Rossato, Marco (Frontiers in Pharmacology, 2023)
The activation of the P2X7 receptor subtype (P2X7R) has a main role in orchestrating the cellular inflammatory response in many different tissues. Obesity is characterized by dysfunctional fat deposition leading to a tissue-specific and systemic low-grade inflammation. Androgens and estrogens contribute to the whole adipose tissue inflammatory state, but the involvement of sex steroids in the purinergic signaling modulation in adipocytes is still unknown. We performed an in-vitro study to evaluate the possible role of sex hormones on the P2X7R gene expression in human adipocytes, at baseline and after stimulation with bacterial lipopolysaccharide (LPS). We evaluated P2X7R gene expression during in vitro differentiation of human adipocytes, in the absence and presence of testosterone (T) and 17β-estradiol (E2) in the presence and absence of LPS. Furthermore, we analyzed the effects of incubation with dihydrotestosterone (DHT), a non-aromatizable androgen, using the co-incubation of isolated human adipocytes with T alone or in combination with anastrozole, an inhibitor of aromatase, the enzyme responsible of T conversion to E2. At baseline, incubation of adipocytes with T or E2 did not significantly affect P2X7R gene expression. On the contrary, the incubation with DHT was associated with a significant reduction of P2X7R gene expression. LPS incubation significantly increased gene expression of P2X7R with respect to baseline. Interestingly, after LPS stimulation, DHT exposure showed an additional effect, markedly increasing the P2X7R gene expression. This amplificatory effect was confirmed by the incubation of adipocytes to both anastrozole and testosterone. In these experimental conditions, while no effect was observed at baseline, an amplification of the expression of the P2X7R mRNA was observed after stimulation with LPS. This is a provisional file, not the final typeset articleThe purinergic system is involved in the inflammatory response of adipocytes, and androgens may modulate its activity. In particular DHT, a non-aromatizable androgen, amplifies the LPSinduced P2X7R gene expression in human adipocytes thus showing a gender regulated response of the expression of this purinergic receptor strongly involved in the inflammatory response in adipose tissue.